Is weak broad ligament a predisposing factor for uterine torsion in dairt buffaloes ? - BRAR, P S; SAIGAL, R P; SHARMA, R D; NANDA, A S (The Indian Journal of Animal Sciences, 2011)
Etiology of uterine torsion, the single major cause of maternal dystocia in buffaloes, is not well understood. The present study examined the microscopic studies of broad ligament in buffaloes to identify the structural abnormalities, if any, as predisposing factor for occurrence of uterine torsion in dairy buffaloes. The investigations were done 011 10 MU1Tah buffaloes having uterine torsion and 7 having fetal causes of dystocia. In each animal 4 biopsies were taken, one each from near to its attachment with ileum at the left and the right side and near to its attachlnent with ovaries at left and right side. Histological examination revealed the broad ligament consisted of double serosal folds containing smooth muscles, blood vessels and connective tissue in between them. The muscular layer under subserosa varied in its density at different sites in different animals. The musculature of broad ligament in sections was highly variable. The relative amount of muscles (at scale 1-10) at left ovarian end, left iliac end, right ovarian end and at right iliac end was 2.95±O.90 vs 6.14 ± 1.71, 2.70±O.77 vs 6.00±1.56, 3.80±l.06 vs 6.86±1.42 and 3.45±O.73 vs 5.50 ± 1.51 in uterine torsion and other forms of dystocia respectively. Syncytium was better developed in buffaloes suffering from fetal causes of dystocia. Prom the above studies it could be concluded that weak broad ligaments predispose the buffaloes to uterine torsion at the time of parturition.